Use of autogenous bone and beta-tricalcium phosphate in maxillary sinus lifting: histomorphometric study and immunohistochemical assessment of RUNX2 and VEGF - Pereira, R. S. [UNESP] (2017)
The aim of this study was to compare the use of beta-tricalcium phosphate (β-TCP) (chronOS) with autogenous bone grafts alone in maxillary sinus elevation surgery. The test samples were β-TCP alone, β-TCP mixed with autogenous bone grafts (1:1), and autogenous bone grafts alone. Twelve maxillary sinuses were grafted with β-TCP (group 1), nine with β-TCP + autogenous bone graft (group 2), and 12 with autogenous bone graft (group 3). After 6 months, biopsies were obtained concurrent to the placement of dental implants; these were subjected to histomorphometric analysis and immunohistochemical analysis for runt-related transcription factor 2 (RUNX2) and vascular endothelial growth factor (VEGF). The average bone formation in group 1 was 46.3 ± 11.6% in the pristine bone region, 47.6 ± 9.9% in the intermediate region, and 44.8 ± 22.1% in the apical region; in group 2, values were 35.0 ± 15.8%, 32.5 ± 13.7%, and 32.8 ± 16.0%, respectively; in group 3, values were 43.1 ± 16.0%, 31.0 ± 13.0%, and 46.1 ± 16.3%, respectively. Immunostaining of samples in group 2 showed high cellular activity and immature bone; this differed from groups 1 and 3, in which mature bone was demonstrated. Thus, this study showed that β-TCP presents the same behaviour as autogenous bone graft, which makes it a good bone substitute.